STUDENTS’ ERRORS IN SOLVING REASONING-BASED CONGRUENCE PROOF PROBLEMS - Scristia Scristia; Siti Aisyah; Meryansumayeka Meryansumayeka; Erna Retna Safitri; Haris Kurniawan (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to describe the difficulties faced by students in solving reasoning problems in the form of proving the triangle congruence. This type of research is descriptive qualitative. The research subjects were 25 students of grades IX in one of the junior high schools in Palembang in the odd semester of the 2021/2022 academic year. Data were obtained from tests conducted in November 2021. The results showed that the errors encountered by students when solving the question of proof of cooperation are: not knowing the symbols in mathematics, failing to grasp the meaning of the problem, weak knowledge of mathematical concepts and principles, being careless, and not being meticulous.Penelitian ini bertujuan untuk mendeskripsikan kesalahan yang dihadapi siswa dalam menyelesaikan masalah penalaran berupa pembuktian kesebangunan segitiga. Metode penelitian ini adalah deskriptif kualitatif. Subjek penelitian ini adalah 25 siswa kelas IX di salah satu SMP di Palembang pada semester gasal tahun pelajaran 2021/2022. Data diperoleh dari tes tertulis yang dilakukan pada bulan November 2021. Hasil penelitian menunjukkan bahwa kesalahan yang dilakukan siswa pada saat menyelesaikan soal pembuktian disebabkan antara lain; kesalahan menulis simbol-simbol matematika, kesalahan konsep berupa kesalahan menangkap makna soal, kesalahan prinsip matematika, dan tidak teliti.